Tomada de consciência em atividades de Modelagem Matemática no Ensino Fundamental - Schrenk, Maykon Jhonatan (2020)
In this qualitative research, we are interested in the take of consciousness, in a metacognitive perspective, of students in the fifth and sixth years of Elementary School while developing mathematical modeling activities. The question that guides this research is: What do students in the fifth and sixth years of elementary school manifest in relation to the Take of Consciousness when reflecting on their ideas and their resolution referrals when investigating a situation through Mathematical Modeling? To answer the question, we defined, as a general objective, to identify, in the manifestations of students of fifth and sixth years of Elementary School, evidence of take of consciousness of their ideas and their resolution referrals, when investigating a situation through Mathematical Modeling. The data collection process took place between October 22, 2018 and November 13, 2018 with participant-observation classes and classes in the development of Mathematical Modeling activities. We take, for the description and analysis of the data, the written records present in the activities developed, the audios of the conversations of the students while developing the activities and the videos made of the classrooms, with the movements, speeches and expressions of the students, in order to complement the audios and written records. As theoretical support, we take Mathematical Modeling in Mathematics Education and the take of consciousness in a metacognitive perspective. The data were analyzed based on Content Analysis and the results of this analysis converged into four categories: i) Take of consciousness manifested in a Mathematical Modeling activity in view of the need for the student to revisit and monitor his cognitive processes; ii) Take of consciousness manifested in a Mathematical Modeling activity due to the mediation activity; iii) Take of consciousness manifested in a Mathematical Modeling activity in the relation that the student establishes with something that is concrete for him; and iv) Specificities in the takes of consciousness manifested in a Mathematical Modeling activity by students of fifth and sixth years. The study points out that, in a Mathematical Modeling activity, when the student becomes aware of his way of learning, the knowledge he already has about a certain content, the relationships he makes and how he acts, overcoming difficulties in the face of a problem-situation is potentiated, as well as its learning. Based on the research, we define take of consciousness in the metacognitive perspective and, more specifically, in the “social metacognition” perspective, as a conscious process of perception about cognitive processes that occurs in the interdependence between mediation activity, knowledge and the cognitive monitoring and the relation that the subject establishes with something concrete for him, while developing activities and dealing with situations involving investigation, involved in the dialogue undertaken within a group, with the purpose of performing a cognitive action.